2022
DOI: 10.1080/17501229.2022.2052298
|View full text |Cite
|
Sign up to set email alerts
|

Prof-teaching: an English-medium instruction professional development program with a digital, linguistic and pedagogical approach

Abstract: The increase of English-medium instruction (EMI) in higher education has encouraged institutions to provide their academic staff with professional development courses. In this paper, we present the case study of Prof-teaching, a comprehensive EMI teacher training program at a Spanish university with a digital, linguistic and pedagogical approach. The main objective is to determine if the program meets the needs of the institution's current and prospective EMI lecturers. For this purpose, the university context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…These remarks seem to be in line with previous work on EMI teacher training programmes and their evaluation in different cultural contexts (e.g. Guarda & Helm, 2011;Morell et al, 2020). Guarda and Helm (2011) reported findings in an Italian context in which a participant stated that "'I have discovered new teaching pathways', which seems to be in line with those reported above by colleagues at our institution.…”
Section: Qualitative Evaluation Of Participantssupporting
confidence: 91%
See 1 more Smart Citation
“…These remarks seem to be in line with previous work on EMI teacher training programmes and their evaluation in different cultural contexts (e.g. Guarda & Helm, 2011;Morell et al, 2020). Guarda and Helm (2011) reported findings in an Italian context in which a participant stated that "'I have discovered new teaching pathways', which seems to be in line with those reported above by colleagues at our institution.…”
Section: Qualitative Evaluation Of Participantssupporting
confidence: 91%
“…There is still a lot of work ahead in developing ICLHE's lecturers support and training at our institution. It is our intention to develop a community of practice that meets and shares experiences in line with suggestions provided by Fortanet-Gómez (2020) and Morell et al (2020), among others. We believe that creating trainees' digital production portfolios can also be an interesting learning experience for ICLHE lecturers who can then apply such resources and principles in their own English-medium teaching context.…”
Section: Final Remarksmentioning
confidence: 87%
“…In addition, professional development should focus on digital tools for faculty who teach in an EMP. Morell et al (2022) suggest that professors should be trained to gain knowledge and skills (in relation to examples of machine translation, style guidelines, phrase-banks, spelling and grammar check) of information technology resources to produce better quality materials and increase their self-confidence when they prepare and teach lessons in online platforms. A review by Querol-Julián and Crawford Camiciottoli (2019) suggests that the role of technology and online learning in EMPs will only increase in the future, so it is important that EMP instructors are provided the necessary professional development in these technologies.…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as being about the ability to make various modalities work together to produce comprehensible meaning (Costa and Mair, 2022). The study of Morell et al (2022a) found that the coordination of multiple modalities in addition to language can provide additional support for students to comprehend not only the content but also the language of instruction. Instructors who coordinated spoken and written language, graphic elements, gestures, and body language were more successful in constructing their concepts and making the classroom more cohesive (Morell et al, 2022b).…”
Section: Communicate Competencementioning
confidence: 99%